Mindset Positif Sebagai Faktor Utama Dalam Mengoptimalkan AI Untuk Hasil Belajar Siswa - Sulistiyani, Nur; Ismanto, Bambang; Nusarastriya, Yosaphat Haris; Rondonuwu, Ferdy S. (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
This study aims to examine positive mindset as a major factor in optimizing the use of artificial intelligence (AI) to improve student learning outcomes in elementary schools. A descriptive qualitative approach was used involving 5th grade students and teachers who use AI technology in learning. Data were obtained through observation, interviews and document studies and to test the validity of the data tested using triangulation of sources and techniques. The results of the study indicate that the use of AI provides significant benefits by increasing personalization of learning, assessment efficiency, and provides significant benefits by increasing personalization of learning, assessment efficiency, and students' understanding of complex concepts. The percentage of student learning outcomes completion increased from 35% to 90% after the implementation of AI-based media. Students' positive mindset plays an important role in maximizing the effectiveness of AI technology, while teachers are the main facilitators in creating a supportive learning environment. However, challenges such as dependence on technology, limited infrastructure, and the need for teacher training need attention. With the right regulations and cooperation between educational institutions, government, and society, AI integration can have an optimal impact on improving the quality of education.